Pengaruh Kompetensi Pemimpin Kristen Terhadap Efektivitas Pelayanan Gereja Kemah Injil Indonesia Daerah Melawi Hilir Kalimantan Barat - Zakaria Zakaria (Sekolah Tinggi Teologi Jaffray Jakarta, 2021)
The purpose of this study was to determine the effect of Christian leader competence on the effectiveness of the ministry of the Gereja Kemah Injil Indonesia Daerah Melawi Hilir Kalimanatan Barat. This research is motivated by the existence of leaders who have served in the Gereja Kemah Injil Indonesia Daerah Melawi Hilir Kalimantan Barat, but do not yet have the competence as Christian leaders. This study uses quantitative methods with 60 respondents as research subjects. The data collection technique was carried out using an experiment to examine the cause and effect relationship. The data for each variable were analyzed using the frequency distribution of the data scores and continued with linearity test analysis. Before analyzing multiple linear regression with SPSS, normality test analysis was performed; The normality test was conducted to test whether the data obtained came from samples that were normally distributed. The results of this study prove that it turns out that the influence of Christian Leaders' Competency in the Gereja Kemah Injil Indonesia Daerah Melawi Hilir Kalimantan Barat is at a high level and tends to be very high. The competence of Christian leaders strongly influences the effectiveness of services at the Gereja Kemah Injil Indonesia Daerah Melawi Hilir Kalimantan Barat.